Is ICE freezing US agriculture? Farm-level adjustment to increased local immigration enforcement - Ifft, Jennifer; Jodlowski, Margaret (Labour economics, 2022)
•We use U.S. farm survey data to study the impact of enhanced immigration enforcement.•A federal program called 287(g) decreased farm labor supply in several counties.•287(g) led to higher farm labor and fuel expenses, but farmland acreage declined.•Machines and native workers did not fully substitute for non-native farm workers. We study the impact of US immigration enforcement through a locally-implemented program known as 287(g) on agriculture using confidential farm-level data and farm census data. We address the endogeneity of program participation by using pre-program county jail occupancy as an instrument. We provide evidence that the agricultural sector experienced limited endogenous technical change in response to the negative labor supply shock caused by increased immigration enforcement. Fuel expenses increased, consistent with predictions of an increase in automated technology by models of endogenous technical change. However, a corresponding decline in agricultural acres and employment and an increase in labor expenditure suggests capital-labor substitution was insufficient to fully offset the impact of the shock.